Analysis of Biodiesel Cotton Seed Oil on Diesel Engine Performance - Semin - Semin; Adhi Iswantoro; Gage Cendekiaji Hadi (International Journal of Marine Engineering Innovation and Research, 2018)
The world crisis of fossil fuel availability encourages the development to explore alternative energy which is possible to replace of fossil fuel use. The use of biodiesel by using plant oil and animal fats is strived to the maximum extent possible, in order to maintain its sustainability. Cotton seed oil (Ceiba Pentandra) is one alternative that can be used as a replacement fuel. There are four advantages of using Cotton seed oil as a substitute fuel which are: produce a low level of pollutant, guaranteed availability, can be used for diesel engines with little or no modification and in certain mixes can incrase engine lubrication that should incrase engine life. The research was conducted through performance test of YANMAR TF85-MH diesel engine using Cotton seed oil biodiesel with mixture of B30, B20 which has be compared with using YANMAR TF85-MH diesel engine. From the results of performance test, it showed that the using of Cotton seed oil give better effect to performance than fossil diesel fuel use on the same engine. The addition of biodiesel Cotton seed percentage into the fuel provide greater maximum power but it provide the higher fuel consumption value